Original Article: Non–Small Cell Lung Cancer - First-Line Afatinib versus Chemotherapy in Patients with Non–Small Cell Lung Cancer and Common Epidermal Growth Factor Receptor Gene Mutations and Brain Metastases. Issue 3 (March 2016) - Schuler, Martin; Wu, Yi‐Long; Hirsh, Vera; O'Byrne, Kenneth; Yamamoto, Nobuyuki; Mok, Tony; Popat, Sanjay; Sequist, Lecia V.; Massey, Dan; Zazulina, Victoria; Yang, James C.‐H.
ABSTRACT : Introduction: : Metastatic spread to the brain is common in patients with non–small cell lung cancer (NSCLC), but these patients are generally excluded from prospective clinical trials. The studies, phase III study of afatinib or cisplatin plus pemetrexed in patients with metastatic lung adenocarcinoma with EGFR mutations (LUX‐Lung 3) and a randomized, open‐label, phase III study of BIBW 2992 versus chemotherapy as first‐line treatment for patients with stage IIIB or IV adenocarcinoma of the lung harbouring an EGFR activating mutation (LUX‐Lung 6) investigated first‐line afatinib versus platinum‐based chemotherapy in epidermal growth factor receptor gene ( EGFR ) mutation‐positive patients with NSCLC and included patients with brain metastases; prespecified subgroup analyses are assessed in this article. Methods: : For both LUX‐Lung 3 and LUX‐Lung 6, prespecified subgroup analyses of progression‐free survival (PFS), overall survival, and objective response rate were undertaken in patients with asymptomatic brain metastases at baseline (n = 35 and n = 46, respectively). Post hoc analyses of clinical outcomes was undertaken in the combined data set (n = 81). Results: : In both studies, there was a trend toward improved PFS with afatinib versus chemotherapy in patients with brain metastases (LUX‐Lung 3: 11.1 versus 5.4 months, hazard ratio [HR] = 0.54, p = 0.1378; LUX‐Lung 6: 8.2 versus 4.7 months, HR = 0.47, p = 0.1060). The magnitude of PFS improvement with afatinib was similar to that observed in patients without brain metastases. In combined analysis, PFS was significantly improved with afatinib versus with chemotherapy in patients with brain metastases (8.2 versus 5.4 months; HR, 0.50; p = 0.0297). Afatinib significantly improved the objective response rate versus chemotherapy in patients with brain metastases. Safety findings were consistent with previous reports. Conclusions: : These findings lend support to the clinical activity of afatinib in EGFR mutation–positive patients with NSCLC and asymptomatic brain metastases.